Factors Relating to Work Motivation on Employees at Pasar Rebo Public Health Center, Bogor Regency in 2021 - Nur Azis (Enrichment : Journal of Management, 2021)
The purpose of this study was to obtain an overview of the relationship between individual characteristics, satisfier factors and dissatisfier factors on the work motivation of Pasar Rebo Public Health Center employees, Bogor Regency in 2021. The study was conducted with a cross sectional approach, the number of samples was 50 people. The data obtained in this study were primary data from questionnaires distributed to nurses. The results of this study indicate that as many as 2% of employees have very good work motivation, 78% of employees have good work motivation and 20% of nurses have poor work motivation. From the bivariate analysis between variables, it was found that those that had a significant relationship with the work motivation of Puskesmas employees were the work itself, responsibilities, salary received and individual potential development.